Gambaran Pengetahuan Glaukoma pada Mahasiswa Kepaniteraan Fakultas Kedokteran dan Ilmu Kesehatan UKRIDA - Santi Anugrahsari; Amanda Damayanti Pabisa; Raemon Alexandro Mau; Ruth Anthea Airin Simanjuntak (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2022)
Knowledge of glaucoma is significant for medical students and later establishes a diagnosis and initial treatment when becoming a doctor. The incidence of glaucoma has increased in the last decades with the increase and the age of the population. This study aims to determine the glaucoma knowledge among the clerks of the FKIK UKRIDA 2020. This study used descriptive research with a cross-sectional. The sampling technique used the total sampling method. This study found that students had sufficient/moderate knowledge (65.1%) about glaucoma, primarily obtained orally from lectures, and some were also obtained by reading literature or textbooks. There is no specific comparison of student age affecting the level of knowledge about glaucoma. Respondents aged 22 to 29 years have varying levels of expertise, from moderate to good knowledge levels. Meanwhile, based on gender, most women have a good level of knowledge (39.%) compared to men (25.4%). In this study, the distribution of respondents was aged 26 years (22.2%), and most of the respondents were female (63.5%). From the results of the study, it was concluded that respondents with a moderate level of knowledge were 65.1%. More respondents and a wider range of students are needed for further research.